TOPICAL STEROID USE IN THE TREATMENT OF RHINOSINUSITIS IN PREGNANT WOMEN: A SCOPING REVIEW (Vietnam Journal of Community Medicine, 2026)
Objective: To analyze the characteristics of studies on the use of topical steroids in the treatment of rhinosinusitis in pregnant women, and to describe the treatment outcomes and safety of topical steroid use during pregnancy.Subjects and Methods: This scoping review included studies retrieved from electronic databases and information sources such as PubMed, Google Scholar, and the library of Hanoi Medical University. A total of 4 studies met the inclusion criteria and were included in the review.Conclusion: Fluticasone propionate did not demonstrate a significant improvement in nasal congestion symptoms compared with placebo (p > 0.05). The use of intranasal fluticasone propionate during pregnancy did not affect adrenal function, with comparable S-cortisol and U-cortisol levels between the fluticasone and placebo groups (p > 0.05). Intranasal fluticasone propionate was shown to be safe for the fetus. Fetal growth parameters on ultrasound (femur length, biparietal diameter) and postnatal outcomes (gestational age at birth, birth weight, and Apgar score) did not differ significantly from those of the control group (p > 0.05).
Keywords: Rhinosinusitis, pregnancy, topical steroids.